Management of Complications from Skin Cancer Reconstruction - Vila, Peter M.; Thomas, J. Regan (Facial Plastic Surgery, 2020)
Reconstruction of facial cutaneous defects from skin cancer surgery is a commonly done procedure in the hands of many facial plastic surgeons. Excellent surgical technique should always be employed to reduce the risk of a poor result. However, complications do occur and can be devastating for both the patient and surgeon. We review a range of postoperative management options, and the evidence for each modality, so that reconstructive surgeons can stay up to date on current literature.
Keywords: postoperative complications; skin cancers; plastic surgery; evidence-based practice; Mohs' surgery